2008
DOI: 10.1534/genetics.107.085779
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Histone Acetyltransferase Mst1 (KAT5) Is an Essential Protein Required for Damage Response and Chromosome Segregation

Abstract: Schizosaccharomyces pombe Mst1 is a member of the MYST family of histone acetyltransferases and is the likely ortholog of Saccharomyces cerevisiae Esa1 and human Tip60 (KAT5). We have isolated a temperaturesensitive allele of this essential gene. mst1 cells show a pleiotropic phenotype at the restrictive temperature. They are sensitive to a variety of DNA-damaging agents and to the spindle poison thiabendazole. mst1 has an increased frequency of Rad22 repair foci, suggesting endogenous damage. Two-hybrid resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 89 publications
5
55
0
Order By: Relevance
“…We found that a mst1-1 allele, which contains a temperature-sensitive L344S mutation (Gomez et al 2008), resulted in heterochromatin spreading past IRC1R even at a permissive temperature, as indicated by the silencing of IRC1RTura4…”
Section: Mst1 Regulates H4k16ac Levels At Ircsmentioning
confidence: 90%
See 2 more Smart Citations
“…We found that a mst1-1 allele, which contains a temperature-sensitive L344S mutation (Gomez et al 2008), resulted in heterochromatin spreading past IRC1R even at a permissive temperature, as indicated by the silencing of IRC1RTura4…”
Section: Mst1 Regulates H4k16ac Levels At Ircsmentioning
confidence: 90%
“…Among the histone acetyltransferases (HATs) in fission yeast, Mst1 is a member of the highly conserved MYST family of HATs, and it forms a complex similar to the NuA4 complex of budding yeast (Gomez et al , 2008Shevchenko et al 2008), which acetylates H4K16 (Lee and Workman 2007). We found that a mst1-1 allele, which contains a temperature-sensitive L344S mutation (Gomez et al 2008), resulted in heterochromatin spreading past IRC1R even at a permissive temperature, as indicated by the silencing of IRC1RTura4…”
Section: Mst1 Regulates H4k16ac Levels At Ircsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this initial collection did not contain Mst1, because this HAT is an essential protein. Therefore, we obtained a previously described thermosensitive (ts) mutant of mst1 (Gomez et al 2008). IF analysis revealed that the nuclear signal obtained with the anti-H3K4ac antibody was greatly reduced when the mst1-ts mutant was switched to the nonpermissive temperature even for a very short period of time (2 h) (Fig.…”
Section: H3k4 Is Modified By Acetylationmentioning
confidence: 99%
“…Moreover, the urg1 + gene was still induced in a strain lacking the mst2 + gene and at the restrictive temperature in a strain with a ts mutation in the mst1 + gene (Gomez et al 2008), indicating that the two HATs of the MYST subfamily that are encoded by these genes are not responsible (at least not alone) for the increase in histone acetylation during gene activation by nitrogen depletion (data not shown). In summary, there was a pronounced nucleosome loss throughout the strongly induced urg1 + gene in response to nitrogen depletion, but the lack of effects of all mutations tested so far suggests that this loss was likely dependent on several redundant nucleosome remodelers and/or other mechanisms that remain to be identified.…”
Section: Nucleosome Loss In Coding Regions During Inductionmentioning
confidence: 99%